Revision Carpal Tunnel Surgery: A 10-Year Review of Intraoperative Findings and Outcomes - Zieske, Lawrence (2013)
PURPOSE: To evaluate intra-operative findings and outcomes of revision carpal tunnel release (CTR) and to identify predictors of pain outcomes. METHODS: A retrospective cohort study was performed of all adult patients undergoing revision CTR between 2001 and 2012. Patients were classified according to whether they presented with persistent, recurrent, or new symptoms. Study groups were compared by baseline characteristics, intra-operative findings, and outcomes (strength, pain). Within each group, changes in postoperative pinch strength, grip strength, and pain from baseline were analyzed. Predictors of postoperative average pain were examined using both multivariable linear regression analyses and univariable logistic regression to calculate odds ratios of worsened/no change in pain. RESULTS: Revision CTR was performed in 97 extremities (87 patients). Symptoms were classified as persistent in 42, recurrent in 19, and new in 36 hands. The recurrent group demonstrated more diabetes and a longer interval from primary CTR and was less likely to present with pain. Incomplete release of the flexor retinaculum and scarring of the median nerve were common intraoperative findings overall. Nerve injury was more common in the new group. Postoperative pinch strength, grip strength, and pain significantly improved from baseline in all groups, apart from strength measures in the recurrent group. Persistent symptoms and more than 1 prior CTR had higher odds of not changing or worsening postoperative pain. Higher preoperative pain, use of pain medication, and worker’s compensation were significant predictors of higher postoperative average pain. DISCUSSION: Carpal tunnel release may not always be entirely successful. Most patients do improve following revision CTR, but a methodical approach to diagnosis and adherence to safe surgical principles are likely to improve outcomes. Symptom classification, number of prior carpal tunnel releases, baseline pain, pain medications, and worker’s compensation status are important predictors of pain outcomes in this population. LEVEL OF EVIDENCE: Therapeutic Level III